Involvement of papain and legumain proteinase in the senescence process of Medicago truncatula nodules. Issue 3 (14th February 2014) - Pierre, Olivier; Hopkins, Julie; Combier, Maud; Baldacci, Fabien; Engler, Gilbert; Brouquisse, Renaud; Hérouart, Didier; Boncompagni, Eric
Summary The symbiotic interaction between legumes and Rhizobiaceae leads to the formation of new root organs called nodules. Within the nodule, Rhizobiaceae differentiate into nitrogen‐fixing bacteroids. However, this symbiotic interaction is time‐limited as a result of the initiation of a senescence process, leading to a complete degradation of bacteroids and host plant cells. The increase in proteolytic activity is one of the key features of this process. In this study, we analysed the involvement of two different classes of cysteine proteinases, MtCP6 and MtVPE, in the senescence process of Medicago truncatula nodules. Spatiotemporal expression of MtCP6 and MtVPE was investigated using promoter– β‐glucuronidase fusions. Corresponding gene inductions were observed during both developmental and stress‐induced nodule senescence. Both MtCP6 and MtVPE proteolytic activities were increased during stress‐induced senescence. Down‐regulation of both proteinases mediated by RNAi in the senescence zone delayed nodule senescence and increased nitrogen fixation, while their early expression promoted nodule senescence. Using green fluorescent protein fusions, in vivo confocal imaging showed that both proteinases accumulated in the vacuole of uninfected cells or the symbiosomes of infected cells. These data enlighten the crucial role of MtCP6 and MtVPE in the onset of nodule senescence.